Forest Guardians, Forest Destroyers: The Politics of Environmental Knowledge in Northern Thailand - Ibna, Md. Anas (ASEAN Journal of Research, 2025)
Forest Guardians, Forest Destroyers: The Politics of Environmental Knowledge in Northern Thailand by Tim Forsyth & Andrew Walker is reviewed by Md. Anas Ibna Rahman